Sports - McComb, David G. (Oxford University Press, 1998)
Sports: An Illustrated History is an engrossing and lively account of the evolution of sports through various civilizations around the world. Historian David McComb uses sports history as a window into world history and society. This lavishly illustrated volume is not limited to the sports we know well and often play in our backyards, on school teams, or playgrounds. McComb describes the ball games of Mesoamerica, Sumo wrestling in Japan, martial arts in China, wrestling in ancient Egypt, the Olympic Games of classical Greece, and the gladiator fights in ancient Rome. He brings to life medieval tournaments and peasant ballgames, tracing the roots of modern sports